Emerging trends and growth of banking frauds in India: a substantial obstacle in the pathway of sustainable development. (5th February 2021) - Sharma, Neha; Sharma, Dhiraj; Aggarwal, Arun
The present research paper examines the increasing trends of fraud in the banking industry. The current research seeks to evaluate the growth and trends of fraud in the public sector and private sector banks in India. The image of the ugly part of the Indian banking system has been tried to analyse in the study. An overall picture of both the public and private banking sectors have been shown here in the research. The research also reveals the inter-sector comparative results from the perspective of fraud in both the sectors in the span of the last 15 years. The results of the study indicate that the public sector banks are suffering from this huge loss of amount due to fraud in banking activities. From the angle of economic growth, it is a huge setback for the whole monetary circle of the Indian economy. The results indicate that in both the sectors that are public sector and private sector banks, the increasing number of fraud cases is a big reason for increasing the amount which is involved in bank fraud cases.